Analysis of Student’s Numeracy Literacy Skill Based on Reflective-Impulsive Cognitive Style - Klau, Maria Fransineti Hoar; Siahaan, Meiva Marthaulina Lestari; Hijriani, Lailin (Hexagon: Jurnal Ilmu dan Pendidikan Matematika, 2024)
The research belongs to a qualitative descriptive study that aims to describe the numeracy literacy skills students grade 8 of State Junior High School of Kota Baru I (SMPN Kota Baru) in terms of their cognitive styles. The subjects of this study were eight students representing students with reflective cognitive styles yet impulsive cognitive styles. Data collection techniques were, matching familiar figure test (MFFT) to classify students based on their cognitive styles, numeracy literacy tests, and interviews. Data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results of this study showed that the level of numeracy literacy skills of reflective students (SR) was respectively SR 1 is 88%, SR 2 is 67%, SR 3 is 79% and SR 4 is 91%. The level of numeracy literacy skills of impulsive students (SI) was respectively SI 1 is 58%, SI 2 is 67%, SI 3 is 50% and SI 4 is 63%. Reflective subjects have a category of high and very high numeracy literacy ability levels while impulsive subjects have a category of medium and high numeracy literacy ability levels. Reflective students need a long time to understand the problem by describing it into a mathematical model so that reflective students excel in the reasoning aspect. Impulsive students tend to be quick in answering questions but pay less attention to the right answers so that impulsive students stand out in the communication aspect.